1999
DOI: 10.3181/00379727-221-44412
|View full text |Cite
|
Sign up to set email alerts
|

Mushrooms, Tumors, and Immunity

Abstract: Medicinal properties have been attributed to mushrooms for thousands of years. Mushroom extracts are widely sold as nutritional supplements and touted as beneficial for health. Yet, there has not been a critical review attempting to integrate their nutraceutical potential with basic science. Relatively few studies are available on the biologic effects of mushroom consumption, and those have been performed exclusively in murine models. In this paper, we review existing data on the mechanism of whole mushrooms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
202
0
9

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(213 citation statements)
references
References 78 publications
2
202
0
9
Order By: Relevance
“…These phytochemicals appear to induce enzymatic detoxification systems, including mixed function oxidase systems and glutathione-S-transferase. 25 In our study, mushroom was shown to have a protective effect on GC, although association of mushroom with GC is controversial in many animal studies [32][33][34][35] and epidemiologic studies. So further studies are needed to prove the anticarcinogenic effect of mushroom.…”
Section: Table V -Odds Ratios Of Gastric Cancer In Relation To Food Gmentioning
confidence: 60%
“…These phytochemicals appear to induce enzymatic detoxification systems, including mixed function oxidase systems and glutathione-S-transferase. 25 In our study, mushroom was shown to have a protective effect on GC, although association of mushroom with GC is controversial in many animal studies [32][33][34][35] and epidemiologic studies. So further studies are needed to prove the anticarcinogenic effect of mushroom.…”
Section: Table V -Odds Ratios Of Gastric Cancer In Relation To Food Gmentioning
confidence: 60%
“…A major problem in characterizing many natural products is that they represent a complex mixture of ingredients, each one of which may contribute to their bioactivity. β-Glucans from fungi, yeast and seaweed are well-known biologic response modifiers that function as immunostimulants against infectious diseases and cancer (Borchers et al, 1999;Brown and Gordon, 2003). Unlike most other natural products, purified β-glucans retain their bioactivity, which permits the characterization of how β-glucans work on a cellular and molecular level.…”
Section: Glucan and Immunological Reactionsmentioning
confidence: 99%
“…PL, after purification, shows a relatively homogeneous molecular weight distribution on gel permeation HPLC and is estimated to be around 150 kDa from the retention time on HPLC pullulan molecular markers (Song et al, 1995). The main components of PL are polysaccharides (Song et al, 1995;Lorenzen and Anke, 1998;Borchers et al, 1999;Han et al, 1999). Many studies demonstrated that polysaccharides from various substances, including PL, are remarkably effective in inhibiting the growth of tumours without toxic side effects.…”
mentioning
confidence: 99%